SOCIO-POLITICAL ESSENCE OF SUPPORTING WOMEN IN SOCIETY (Scientific journal of the Fergana State University, 2023)
This article reveals the theoretical and practical significance of increasing women's activity in socio-political processes during the implementation of reforms in our country. In this process, the need for promotion as a result of education and moral promotion is based. In the thinking of women and girls, in understanding the basic content, goals and implementation mechanisms of the reforms implemented in our country, instead of gender politics, increasing their activity in the reforms has been revealed from a socio-philosophical point of view.